Quality Minimization of Agricultural Drainage Water for Irrigation Water Reuse Using Coconut Shell Activated Carbon - M. A. Adejumobi; R. A. Olaoye; T. B. Adebayo; O. E. Onofua (Archives of Current Research International, 2022)
Nutrients and organic pollutants draining from agricultural fields are the leading sources of surface water quality impairment. Activated carbon (AC) produced from agricultural crop residues has great success in the sequestration of hazardous substances from wastewaters. This study evaluates the potential of coconut shell activated carbon for agricultural drainage water quality minimization; pH adjustment, and excess nitrate and sulphate adsorption. Agriculture drainage water samples were collected and analyzed for Electrical conductivity, Total Dissolved Solids, Chloride, Sodium, Sulphate, Bicarbonate, Nitrate – Nitrogen, and pH. Coconut shells were sourced locally and carbonized at 500°C (± 5°C) for one hour in a muffle furnace. The char produced was ground, sieved, and activated with potassium hydroxide (KOH). The porosity and morphological structures of the AC were examined using a Scanning Electron Microscope. The effect of contact time (30, 60, 90, and 120 min), temperature (20 and 40°C), and adsorbent dosage (1, 1.5, 2, and 2.5 g) were examined using batch studies. The analysis of the drainage water shows the water is highly alkaline and contains sulphate and nitrate above FAO benchmark values. The SEM analysis indicates that the stability and mesoporosity of the carbonaceous material were enhanced by KOH activation. The pH value of the treated water decreased from 9.94 (highly alkaline) to 7.92. The use of 1 g (10 g/l) of coconut shell AC has the highest amount of nitrate and sulphate per unit quantity of AC (4.1 and 2.98 mg/g respectively). The adsorption process peaked at 30 mins contact time with 99.8% and 98.8% nitrate and sulphate removal efficiency, respectively. The process is temperature dependent; nitrate adsorption performs slightly better at 40°C; sulphate adsorption at 20°C. More research effort is needed to ascertain the performance and applicability under continuous flow conditions.